Gestión de compras internacionales y stock óptimo de la empresa Inversiones Díaz E.I.R.L. año 2024 - Ríos Niño de Guzmán, Janeth del Pilar (2025)
In today's globalized context, companies face the challenge of optimizing their international purchasing processes to ensure the timely and efficient supply of inputs and products, while maintaining an optimal stock that minimizes costs and maximizes profitability. International purchases have a significant impact on importing companies, both strategically and logistically. From a strategic perspective, companies must develop a clear vision of their import objectives, identify reliable suppliers abroad, negotiate competitive prices, and establish solid business relationships. Logistically, companies must efficiently manage the international supply chain, including transportation, warehousing, customs clearance, and distribution of imported products. This research described and related the variables of International Purchasing Management and Optimal Stock in the company Inversiones Díaz E.I.R.L. in the year 2024. The methodology used for the study was quantitative, with a descriptive-correlational level of study, applied non experimental type, and cross-sectional. The study population considered 18 workers (02 officials, 04 sales managers, and 12 sales advisors). The sampling used was census type, the instrument used for data collection was the questionnaire, obtaining an excellent Cronbach's Alpha coefficient of 0.945. The results were analyzed in two statistical groups. In the descriptive, it was obtained that in Variable 1: International Purchasing Management, 78% rated it as good and 22% considered it regular. In Variable 2: Optimal Stock, 72% evaluated it as good, while 28% perceived it as regular. In the inferential, using Pearson's r parametric statistic, a very strong direct correlation coefficient of 0.893 was obtained, with a 2-tailed sig. of 0.000, for which the general hypothesis Hi is accepted, which implies the existence of a positive and significant relationship between international purchasing management and optimal stock in the company Inversiones Díaz E.I.R.L. in 2024. It is concluded that there is a clear deficiency in the processes determined for good international purchasing management, and therefore it cannot be considered that the company maintains an optimal stock of merchandise, and therefore one variable depends on the other.